Plant diversity - Gow, Tracy; Spears, Madeleine ([United States] : Insight Media, 1995)
Discusses the evolution of plants from water to land, focusing on the differences between bryophytes and tracheophytes, between angiosperms and gymnosperms, and between monocots and dicots
Editor, Richard Taunton
Keywords: Plant diversity